Valuing of Liquidity Investment Value - Kozyr, Yuriy V. (Archives of Business Research, 2020)
This paper provides a solution to the problem of investment choice between cash and income-generating assets and also describes a possible approach to valuation the relative and absolute value of liquidity in such a situation.